Unveiling Sedimentation Hiatuses: Key Factors in Hydrocarbon Reservoir Formation in Azerbaijan - Ahmadov, Tofig; Namazli, Nurlan (Anuário do Instituto de Geociências, 2025)
In recent decades, the decline of oil and gas reserves in traditional anticline traps has become a pressing issue for many hydrocarbon-producing regions worldwide, including Azerbaijan. This situation has directed the focus of geologists and geophysicists toward identifying alternative hydrocarbon sources, particularly in non-anticlinal traps. This paper aims to explore the geological and geophysical characteristics of sedimentation hiatuses, which manifest as surfaces and play a crucial role in the formation of hydrocarbon traps by significantly influencing hydrocarbon accumulation and migration processes. The study emphasizes the essential methodologies employed in seismic exploration to investigate sedimentation hiatuses. It establishes that these hiatuses are predominantly associated with strong seismic horizons that lack weak boundaries, facilitating their identification in seismic data. The research elaborates on the impact of sedimentation hiatuses on the acoustic properties of reservoirs, underscoring their influence on filtration and capacity characteristics. The analysis also highlights the independence of phase and lithological components within the wave field, indicating that while lithological components are well-studied, the phase components associated with sedimentation breaks require further exploration. Overall, this research provides valuable insights into the complex geological features that influence hydrocarbon reservoirs, underscoring the necessity for advanced techniques in seismic interpretation and exploration.